O movimento social cáritas na luta pela melhoria da educação do campo nas ilhas de Abaetetuba-PA - SENA, Leonice Dias (2019)
The article refers to the Cáritas social movement in the islands of Abaetetuba-PA, organized by ParóquiaRainha da Paz. It is a worldwide movement of the Catholic Church. In this article we show how it organizes itself internationally to the region researched, emphasizing its structure until the work in the Islands, because it works with compassion and professionalism, to respond to emergencies, promote development and defend a more just world, where all are equal. Cáritas in the Islands has been working for improvements from health to public safety, but will be specifically presented its action in the field education, which is already lacking in urban centers, the more in the Islands is of poor quality, lacking since qualified teachers to work in the field.